ANALISIS TEMA FANTASI GAMBARAN PERAN PEREMPUAN IDEAL DALAM SERIES IKLAN KECAP SEDAAP - Marta Alya Shinta; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Kecap Sedaap is one of the most popular soy sauce brand in Indonesia. This brand is one of many domestic brands that depict family life and domestic activities in its advertisements. In its ad campaigns, women are often potrayed engaging in cooking, family caring, and domestic chores. This representation raises an issue because domestic work is not only showed as a daily activity but also as a symbol of the ideal standar for woman, particularly in the family. This study will focus on using Fantasy Theme Analysis to examine the chain of female fantasies in interpreting the construction of the ideal female role in the Kecap Sedaap advertisement series. The main theory to be used in this study is Symbolic Convergence Theory. This study employs a qualitative descriptivce approach, utilizing text analysis and in-depnth intewview as data collection techniques. The study will examine three Kecap Sedaap advertisements and invlolve eight informants comprising teenagers, adults, married woman, and mothers-in-law. The result of this study indicate that advertisement contribute to constructing an ideal image of women through three fantasy types. First, cooking skills are portrayed as a source of pride for woman. Second, cooking skills are presented as a standard for a woman’s acceptability, particulary for women who are prospective daughters-in-law. Third, cooking si portrayed as a means for a mother to express her love. Audience reception shows both drawing and and loosing fantasy chain. Drawing fantasy chain appears when informants intepret cooking as a familiar expression of love and care. Most informants are able to undertand that food and cooking can symbolize affection within the family. This indicate that such an ads can still contribute to how individual responding to sosial construction about ideal woman role which is related to cooking as a normal way to show an act of love.